2017
DOI: 10.1016/j.ajhg.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Decreased STARD10 Expression Is Associated with Defective Insulin Secretion in Humans and Mice

Abstract: Genetic variants near ARAP1 (CENTD2) and STARD10 influence type 2 diabetes (T2D) risk. The risk alleles impair glucose-induced insulin secretion and, paradoxically but characteristically, are associated with decreased proinsulin:insulin ratios, indicating improved proinsulin conversion. Neither the identity of the causal variants nor the gene(s) through which risk is conferred have been firmly established. Whereas ARAP1 encodes a GTPase activating protein, STARD10 is a member of the steroidogenic acute regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
69
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 78 publications
18
69
2
Order By: Relevance
“…The characteristic decrease of plasma proinsulin:insulin ratio observed in human carriers of the risk alleles at this locus [22], and the observation of a similar phenotype in βStard10KO mice [10], suggest an action of STARD10 on proinsulin processing in the β-cell. We therefore next investigated this hypothesis by performing a metabolic labelling pulse-chase experiment in isolated islets from WT and βStard10KO mice.…”
Section: Newly Synthesised Proinsulin Is Constitutively Secreted By βmentioning
confidence: 88%
See 3 more Smart Citations
“…The characteristic decrease of plasma proinsulin:insulin ratio observed in human carriers of the risk alleles at this locus [22], and the observation of a similar phenotype in βStard10KO mice [10], suggest an action of STARD10 on proinsulin processing in the β-cell. We therefore next investigated this hypothesis by performing a metabolic labelling pulse-chase experiment in isolated islets from WT and βStard10KO mice.…”
Section: Newly Synthesised Proinsulin Is Constitutively Secreted By βmentioning
confidence: 88%
“…Mice homozygous for floxed Stard10 (Stard10 fl/fl ) alleles were crossed to mice expressing Cre recombinase from the endogenous Ins1 locus (Ins1-Cre mice). This generated Stard10 fl/fl :Ins1Cre + (βStard10KO) mice as in [10].…”
Section: Generation and Use Of Stard10 Null Micementioning
confidence: 99%
See 2 more Smart Citations
“…We observed significant activity of the TC element that overlaps rs1552224 in our STARR-seq assay (Z score = 4.90, Z score P value = 4.78x10 -7 ). A previous study showed evidence for rs11603334 to be the causal variant (Kulzer et al 2014), whereas another study pointed towards an indel rs140130268 as more likely causal (Carrat et al 2017). These studies nominating different causal variants highlight the complexity at this locus.…”
Section: Cage Profiles Augment Functional Genomic Annotations To Bettmentioning
confidence: 85%